2017
DOI: 10.2527/jas.2016.1110
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multi drug antimicrobial resistance in Mannheimia haemolytica isolated from high-risk stocker cattle at arrival and two weeks after processing1

Abstract: Bovine respiratory disease (BRD) is the leading cause of morbidity and mortality in North American beef cattle. () is the bacterial pathogen most frequently isolated from cattle with BRD and the prevalence of antimicrobial resistance in this pathogen has been increasing. Administration of antimicrobials to prevent BRD is commonplace in stocker cattle, but the impact of this practice on emergence of resistance in is unknown. High risk, sale barn origin bull and steer calves ( = 169) were transported to a stocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 33 publications
4
26
0
Order By: Relevance
“…The overall picture suggests that some of the M. haemolytica ICE sequences are of older origin and were acquired before those found in P. multocida . In the case of the strains isolated from cattle, this is consistent with M. haemolytica being a primary etiologic agent associated with BRD (Klima et al, 2016 ; Snyder et al, 2017 ).…”
Section: Discussionsupporting
confidence: 57%
“…The overall picture suggests that some of the M. haemolytica ICE sequences are of older origin and were acquired before those found in P. multocida . In the case of the strains isolated from cattle, this is consistent with M. haemolytica being a primary etiologic agent associated with BRD (Klima et al, 2016 ; Snyder et al, 2017 ).…”
Section: Discussionsupporting
confidence: 57%
“…In North America, there is a trend toward increasing frequencies of MDR in pathogens involved in high mortality BRD cases ( 6 , 8 , 24 , 25 ). Recent reports examining the molecular basis for AMR in Pasteurellaceae strains from BRD mortalities indicate that large mobile elements, linking arrays of resistance genes together, are present in both American and Canadian fed cattle populations ( 10 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…) and the US (Snyder et al . ) showed significantly high levels of resistance (≥50%) in M. haemolytica , P. multocida and H. somni isolated from the respiratory tract of feedlot cattle, with some bacteria resistant against multiple classes of antibiotics. Therefore, novel strategies are needed to reduce antimicrobial use and to mitigate antimicrobial‐resistant respiratory pathogens in beef cattle.…”
Section: Introductionmentioning
confidence: 99%
“…However, multidrug resistance in bacterial respiratory pathogens isolated from feedlots has increased in the last decade (Portis et al 2012), including the emergence of bacterial pathogens that are resistant to several classes of antibiotics used for both the control and treatment of BRD (Noyes et al 2015). Recent studies conducted in commercial feedlots in Canada (Anholt et al 2016;Timsit et al 2017) and the US (Snyder et al 2017) showed significantly high levels of resistance (≥50%) in M. haemolytica, P. multocida and H. somni isolated from the respiratory tract of feedlot cattle, with some bacteria resistant against multiple classes of antibiotics. Therefore, novel strategies are needed to reduce antimicrobial use and to mitigate antimicrobial-resistant respiratory pathogens in beef cattle.…”
Section: Introductionmentioning
confidence: 99%